2020
DOI: 10.1093/jrs/feaa003
|View full text |Cite
|
Sign up to set email alerts
|

Hope Among Refugee Children Attending the International School of Peace on Lesbos

Abstract: The study focuses on refugee children who live in a temporary transit camp on the Island of Lesbos in Greece, and attend a unique school, which, in the camp’s temporary conditions, endeavours to provide the children with safety, security, and an adaptive learning experience. It examines hope among the refugee children by means of the Children’s Hope Scale (Snyder, 1997), which was administered to 132 children aged 6-16 who attend the school. The general hope scores among the refugee children were similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Furthermore, in the research carried out by Aydın-Sünbül and Arslan-Gördesli (2020), The study found a significant positive relationship between self-compassion and hope in guardians with special needs children, and between hope and psychological resilience. It is among the results obtained from the studies (Ai et al, 2007;Ben-Asher et al, 2020;Cortes-Buchanan, 2007;Çiltaş, 2019;Eggerman and Panter-Brick, 2010;Erarslan, 2014;Eseoğlu, 2021;Goodman, 2004;Sleijpen et al, 2016) The study indicates a significant positive correlation between hope and psychological resilience. Based on theoretical explanations and these studies, it can be said that psychological resilience, hope, and self-compassion can be concepts that come into contact with each other, and therefore it is important to examine them together.…”
mentioning
confidence: 59%
“…Furthermore, in the research carried out by Aydın-Sünbül and Arslan-Gördesli (2020), The study found a significant positive relationship between self-compassion and hope in guardians with special needs children, and between hope and psychological resilience. It is among the results obtained from the studies (Ai et al, 2007;Ben-Asher et al, 2020;Cortes-Buchanan, 2007;Çiltaş, 2019;Eggerman and Panter-Brick, 2010;Erarslan, 2014;Eseoğlu, 2021;Goodman, 2004;Sleijpen et al, 2016) The study indicates a significant positive correlation between hope and psychological resilience. Based on theoretical explanations and these studies, it can be said that psychological resilience, hope, and self-compassion can be concepts that come into contact with each other, and therefore it is important to examine them together.…”
mentioning
confidence: 59%
“…A study among 132 URMs aged six to sixteen in a temporary transit camp International Journal of Social Quality on Lesvos revealed that they experienced afternoon schoolwork as a "hopeful" space. Here children function as normal students in a safe environment, enabling growth in cognitive, emotional, and interpersonal realms (Asher et al 2021). Group work and community meetings in shelters and SILs are held to promote the sense of belonging and solidarity.…”
Section: Trust and Hope As Basic Drivers Of Belongingmentioning
confidence: 99%
“…Hope indicates that we recognise and act on a tendency existing in the present reality that has the capacity to change which leads us towards a potential future (Anderson & Holden, 2008;Anderson & Fenton, 2008). Hope, however, is not utopian but better conceived as action-directed and a temporal vector that points from the present into the future from a specific location with specific direction and force (Anderson, 2002;Ben Asher et al, 2020;Shaker & Ahmadi, forthcoming). As a component of resilience or a mediator of resilience, hope and 'doing hope' improve capacities to manage changes through enhancing coping skills (Collins, 2015;Ben Asher et al, 2020).…”
Section: Avenues Of Possibilitymentioning
confidence: 99%
“…Hope, however, is not utopian but better conceived as action-directed and a temporal vector that points from the present into the future from a specific location with specific direction and force (Anderson, 2002;Ben Asher et al, 2020;Shaker & Ahmadi, forthcoming). As a component of resilience or a mediator of resilience, hope and 'doing hope' improve capacities to manage changes through enhancing coping skills (Collins, 2015;Ben Asher et al, 2020). In this regard, Appadurai (2013) has called for 'politics of hope,' a politics of possibilities to come.…”
Section: Avenues Of Possibilitymentioning
confidence: 99%